IL-15 Activates the Jak3/STAT3 Signaling Pathway to Mediate Glucose Uptake in Skeletal Muscle Cells - Krolopp, James E.; Thornton, Shantaé M.; Abbott, Marcia J. (Frontiers in Physiology, 2016)
Myokines are specialized cytokines that are secreted from skeletal muscle (SKM) in response to metabolic stimuli, such as exercise. Interleukin-15 (IL-15) is a myokine with potential to reduce obesity and increase lean mass through induction of metabolic processes. It has been previously shown that IL-15 acts to increase glucose uptake in SKM cells. However, the downstream signals orchestrating the link between IL-15 signaling and glucose uptake have not been fully explored. Here we employed the mouse SKM C2C12 cell line to examine potential downstream targets of IL-15-induced alterations in glucose uptake. Following differentiation, C2C12 cells were treated overnight with 100 ng/ml of IL-15. Activation of factors associated with glucose metabolism (Akt and AMPK) and known downstream targets of IL-15 (Jak1, Jak3, STAT3, and STAT5) were assessed with IL-15 stimulation. IL-15 stimulated glucose uptake and GLUT4 translocation to the plasma membrane. IL-15 treatment had no effect on phospho-Akt, phospho-Akt substrates, phospho-AMPK, phospho-Jak1, or phospho-STAT5. However, with IL-15, phospho-Jak3 and phospho-STAT3 levels were increased along with increased interaction of Jak3 and STAT3. Additionally, IL-15 induced a translocation of phospho-STAT3 from the cytoplasm to the nucleus. We have evidence that a mediator of glucose uptake, HIF1α, expression was dependent on IL-15 induced STAT3 activation. Finally, upon inhibition of STAT3 the positive effects of IL-15 on glucose uptake and GLUT4 translocation were abolished. Taken together, we provide evidence for a novel signaling pathway for IL-15 acting through Jak3/STAT3 to regulate glucose metabolism.